The effect of dabigatran on the activated partial thromboplastin time and thrombin time as determined by the Hemoclot thrombin inhibitor assay in patient plasma samples - Hapgood, Greg; Butler, Jenny; Malan, Erica; Chunilal, Sanjeev; Tran, Huyen (Thrombosis and Haemostasis, 2013)
Dabigatran is an oral direct thrombin inhibitor that does not require routine laboratory monitoring. However, an assessment of its anticoagulant effect in certain clinical settings is desirable. We examined the relationship between dabigatran levels, as determined by the Hemoclot thrombin inhibitor assay (HTI), the thrombin time (TT) and the activated partial thromboplastin time (aPTT) using different reagents. We describe these parameters with the clinical outcomes of patients receiving dabigatran. Seventy-five plasma samples from 47 patients were analysed. The HTI assay was established to measure dabigatran level. aPTTs were performed using TriniCLOT aPTT S reagent (TC) and three additional aPTT reagents. From linear regression lines, we established the aPTT ranges corresponding to the therapeutic drug levels for dabigatran (90–180 ng/ml). The aPTT demonstrated a modest correlation with the dabigatran level (r= 0.80) but the correlation became less reliable at higher dabigatran levels. The therapeutic aPTT ranges for reagents were clinically and statistically different compared with our reference reagent (46–54 s (TC) vs 51–60 s (SP), 54–64 s (SS) and 61–71 s (Actin FS) (p<0.05)). The TT was sensitive to the presence of dabigatran with a level of 60 ng/ml resulting in a TT > 300 s. In conclusion, the aPTT demonstrated a modest correlation with the dabigatran level and was less responsive with supra-therapeutic levels. aPTT reagents differed in their responsiveness, suggesting individual laboratories must determine their own therapeutic range for their aPTT reagent. The TT is too sensitive to quantify dabigatran levels, but a normal TT suggests minimal or no plasma dabigatran.
Keywords: Dabigatran; activated thromboplastin time (aPTT); thrombin time (TT); hemoclot thrombin inhibitor assay (HTI); laboratory monitoring